Effect of Silica Modulus on Concrete Maturity at Different Curing Temperatures - Ibrahim, Eman Kh.; Ahmed, Sofyan Y.; Salih, Oday Asal (Salehan Institute of Higher Education, 2026)
The variation in early-age strength development of concrete mixes containing locally produced OPC, cured at different temperatures throughout the seasons, has motivated many researchers to investigate this issue. This study analyzed how differences in the constituents of locally sourced OPC, particularly the silica modulus, affect strength development and its impact on concrete maturity at various temperatures. Concrete maturity was calculated using strength development over time to determine an equivalent age required to achieve a specific strength at a standard temperature. The equivalent age is a vital factor for determining the appropriate time to remove formwork at construction sites or to open roads to traffic. The study experimentally evaluated three different proportions of OPC constituents, producing three silica modulus (S.M.) values of 2.4, 2.7, and 3.0. It compared the effect of S.M. variation for two cement contents by assessing two groups of concrete with compressive strengths of 20 N/mm² and 35 N/mm², cured at temperatures of 7, 20, and 35 °C. The results revealed that strength increased with increasing curing temperature at all ages, while the rate of strength development decreased as S.M. increased for both strength levels. In contrast, the activation energy of concrete increased with increasing S.M., with the greatest increase observed in concrete with the higher cement content (35 N/mm²). The maturity function results, expressed in terms of equivalent age for concrete cured at non-standard temperatures (7 and 35 °C), showed that equivalent age was influenced by variations in the OPC S.M., with the effect being more pronounced at S.M. = 2.4 compared with S.M. values of 2.7 and 3.0.